The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula - Ranjith, A.p.; Belokobylskij, Sergey A.; Sureshan, P.m.; Nasser, M. (Zootaxa, 2020)
The ecphyline genus Aivalykus Nixon, 1938 is discussed. A new species, A. microaciculatus Ranjith et Belokobylskij, sp. nov. from India and United Arab Emirates is described and illustrated. A key to all extant species of the genus Aivalykus is provided.